2015
DOI: 10.7326/m14-2238
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Commercial Weight-Loss Programs

Abstract: Background Commercial or proprietary weight loss programs are popular obesity treatment options; however, their efficacy is unclear. Purpose To compare weight loss, adherence, and harms of commercial or proprietary weight loss programs to control/education or behavioral counseling among adults with overweight and obesity. Data sources MEDLINE and Cochrane Database of Systematic Reviews from inception to November 2014; references identified by programs Study selection Randomized controlled trials (RCT) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
181
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 297 publications
(190 citation statements)
references
References 81 publications
(76 reference statements)
5
181
2
2
Order By: Relevance
“…Overall, studies have consistently shown a modest weight loss with commercial weight-loss programs. A 2015 systematic review of 45 studies on the efficacy of commercial weight-loss programs found a 2.9% greater weight loss with Weight Watchers and 4.9% with Jenny Craig compared to control education (no intervention, printed material only, or health education in less than 3 sessions) at 12 months [64]. Other programs that focus on low-calorie meal replacement including Health Management Resources, Medifast, and OPTIFAST and the self-directed Atkins diet similarly achieved greater weight loss than control education but these studies used short-term follow-up of 6 months or less.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, studies have consistently shown a modest weight loss with commercial weight-loss programs. A 2015 systematic review of 45 studies on the efficacy of commercial weight-loss programs found a 2.9% greater weight loss with Weight Watchers and 4.9% with Jenny Craig compared to control education (no intervention, printed material only, or health education in less than 3 sessions) at 12 months [64]. Other programs that focus on low-calorie meal replacement including Health Management Resources, Medifast, and OPTIFAST and the self-directed Atkins diet similarly achieved greater weight loss than control education but these studies used short-term follow-up of 6 months or less.…”
Section: Introductionmentioning
confidence: 99%
“…Other programs that focus on low-calorie meal replacement including Health Management Resources, Medifast, and OPTIFAST and the self-directed Atkins diet similarly achieved greater weight loss than control education but these studies used short-term follow-up of 6 months or less. Other self-directed diets including SlimFast have had mixed results [64]. In a randomized trial of multiple diets, all diet groups achieved a statistically significant change in baseline weight at 1 year following enrollment and there was no difference among the diet groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 These commercial programs incorporate group sessions (eg, Weight Watchers) or more expensive 1-on-1 counselling.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue, Gudzune and colleagues reviewed the evidence on the efficacy of commercial weight-loss programs that focused on nutrition and incorporated behavioral counseling or social support components, regardless of whether physical activity was emphasized (4). Of the 32 programs they identified, they found clinical trial data on only 11, and a minority of the 45 relevant trials lasted 12 months or longer.…”
mentioning
confidence: 99%